**by hand**?

Note the (can be conveniently seen with dominion of Sarrus)$$ \beginvmatrix x & y & z \\ z & x & y \\ y & z & x \\ \endvmatrix=x^3+y^3+z^3-3xyz$$

On the various other hand, the is equal to (if we add to the an initial row 2 various other rows)$$ \beginvmatrix x+y+z & x+y+z & x+y+z \\ z & x & y \\ y & z & x \\ \endvmatrix=(x+y+z)\beginvmatrix 1 & 1 & 1 \\ z & x & y \\ y & z & x \\ \endvmatrix=(x+y+z)(x^2+y^2+z^2-xy-xz-yz)$$ just as we wanted. The last equality complies with from the development of the determinant by very first row.

You are watching: Factor x^3-y^3

share

point out

monitor

answer Dec 27 "13 in ~ 15:17

ElensilElensil

1,00366 silver badges1313 bronze title

$\endgroup$

1

include a comment |

17

$\begingroup$

Consider the polynomial $$(\lambda - x)(\lambda - y)(\lambda - z) = \lambda^3 - a\lambda^2+b\lambda-c\tag*1$$We know$$\begincasesa = x + y +z\\ b = xy + yz + xz \\ c = x y z\endcases$$ substitute $x, y, z$ for $\lambda$ in $(*1)$ and also sum, us get$$x^3 + y^3 + z^3 - a(x^2+y^2+z^2) + b(x+y+z) - 3c = 0$$This is equivalent to$$\beginalign x^3+y^3+z^3 - 3xyz= & x^3+y^3+z^3 - 3c\\= & a(x^2+y^2+z^2) - b(x+y+z)\\= & (x+y+z)(x^2+y^2+z^2 -xy - yz -zx)\endalign$$

share

mention

monitor

reply Oct 29 "13 at 11:16

achille huiachille hui

114k66 yellow badges158158 silver badges311311 bronze title

$\endgroup$

2

include a comment |

17

$\begingroup$

\beginalignx^3+y^3+z^3-3xyz\\&= x^3+y^3+3x^2y+3xy^2+z^3-3xyz-3x^2y-3xy^2\\&= (x+y)^3+z^3-3xy(x+y+z)\\&= (x+y+z)((x+y)^2+z^2-(x+y)z)-3xy(x+y+z)\\&= (x+y+z)(x^2+2xy+y^2+z^2-yz-xz-3xy)\\&= (x+y+z)(x^2+y^2+z^2-xy-yz-zx)\endalign

re-superstructure

cite

follow

edited Aug 23 at 21:40

who

13477 bronze title

answered Oct 29 "13 at 10:23

yuriusyurius

3,6311414 silver badges2020 bronze badges

$\endgroup$

include a comment |

11

$\begingroup$

Use Newton"s identities:

$p_3=e_1 p_2 - e_2 p_1 + 3e_3$ and so $p_3-3e_3 =e_1 p_2 - e_2 p_1 = p_1(p_2-e_2)$ as required.

Here

$p_1= x+y+z = e_1$

$p_2= x^2+y^2+z^2$

$p_3= x^3+y^3+z^3$

$e_2 = xy + xz + yz$

$e_3 = xyz$

re-publishing

point out

monitor

edited Oct 29 "13 in ~ 11:31

achille hui

114k66 gold badges158158 silver badges311311 bronze title

answered Oct 29 "13 at 10:29

lhflhf

205k1313 gold badges216216 silver badges508508 bronze title

$\endgroup$

include a comment |

11

$\begingroup$

A polynomial native $\ptcouncil.netbbQ

So we can try our techniques to factor a polynomial of degree 3 end an integral domain:If it can be factored climate there is a element of level $1$, we call it $z-u(x,y)$ and $u(x,y)$ divides the continuous term that $p(z)$ i beg your pardon is $x^3+y^3$. The latter is have the right to be factored come $(x+y)(x^2-xy+y^2)$ We check each that the feasible values $(x+y), -(x+y), (x^2-xy+y^2), -(x^2-xy+y^2)$ because that $u(x,y)$ and also find that only $p(-x-y)=0$. Therefore $z-(-x-y)$ is a factor.

**Note:**

One deserve to use Kronecker"s technique

to mitigate the administrate of a polynomial that $\ptcouncil.netbbQThis factoring is possible in a finite number of steps but the variety of steps may end up being to high for valuable purpose.

See more: How To Get Stars In Mario Kart Wii ? How Do You Get Stars

An integral domain is a commutative ring v $1$, where the adhering to holds:$$a \ne 0 \land b \ne 0 \implies abdominal muscle \ne 0$$For polynomials $f$, $g$, $h$ $\in I